Assessment of Bacteriological Quality and Identification of Chlorine-Tolerant Bacteria from Different Potable Water Sources in Girei, Nigeria (Stamford Journal of Microbiology, 2024)
Domestic water sources such as wells, taps, and rivers are often used for drinking, cooking, and other household purposes, particularly in rural and peri-urban areas however in most places, their microbiological quality is not always ensured. In this study, 45 water samples were collected from key domestic water sources; 20 each from wells and taps, and 5 from River Benue in Girei, Nigeria following standard sampling techniques. Total aerobic bacterial count (in CFU/mL) for each sample was determined and river water had the highest average microbial count (285), followed by well water (248), and tap water had the lowest count (181). Identification of isolates involved cultural characteristics, Gram staining, motility, and biochemical tests. Bacterial species associated with the water sources were Acinetobacter sp., Aeromonas sp., Bacillus subtilis, Citrobacter, Escherichia coli, Enterococcus faecalis, Enterobacter sp., Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus sp., Providencia sp., Staphylococcus aureus, Staphylococcus epidermidis, Salmonella sp. and Serratia sp.. Chlorine tolerant isolates were determined after treating each sample with 9.9 mg/L (9.9 ppm) of Sodium hypochlorite (NaOCl) at a contact time of 30 minutes. They include 13 isolates from 9 genera, viz:  Acinetobacter sp., B. subtilis, Citrobacter sp., E. coli, Enterobacter sp., K. pneumoniae, P. aeruginosa, Proteus sp. and Serratia sp. By subjecting the treatment tolerant isolates to higher concentrations of NaOCl, results indicated that high concentrations are required to neutralize the isolates with the highest bactericidal concentration observed in B. subtilis (70 ppm), and the lowest was 40 ppm observed in Serratia sp. and E. coli. The findings highlight significant bacterial contamination in water sources, some of which are pathogenic and chlorine-tolerant, emphasizing the need for proper water treatment methods, such as boiling, before consumption by residents.Stam. J. Microbiol. 2024;14(1):5-12